Geometrical Optimization and Thermal‐Stability Characterization of Te‐Free Thermoelectric Modules Based on MgAgSb/Mg3(Bi, Sb)2. Issue 24 (28th April 2022) - Ying, Pingjun; Reith, Heiko; Nielsch, Kornelius; He, Ran
Abstract: Solid‐state thermoelectric (TE) technology is a promising approach to harvest low‐grade waste heat (<573 K) and converts it to useful electricity in industrial and civilian settings. After decades of efforts in improving the figure‐of‐merit ( zT ) of TE materials, the development of advanced modules has started springing up in recent years. Although high‐performance modules have been largely reported based on the successful material improvement, it remains less investigated how and whether the module‐level designs can further increase the conversion efficiency. Herein, following the recent demonstration of a tellurium (Te)‐free TE generator, an increase is demonstrated in the efficiency by reducing both the electrical and thermal energy losses through simply optimizing geometric factors of filling factor and leg‐pair numbers. These module‐level optimizations enable a record conversion efficiency of 8.2% under a ∆ T  ≈ 260 K, thus fulfilling 90% of the theoretical efficiency of the materials and solidly exceeding the Bi2 Te3 modules. Furthermore, module robustness against > 10 160 thermal cycles while preserving a relative efficiency of 95% is demonstrated. These findings highlight the importance of the optimization strategy at the module level and demonstrate the feasibility of using Te‐free thermoelectric compounds to harvest the omnipresent low‐grade heat. Abstract : By optimizing the geometrical configurations of thermoelectric modules based on MgAgSb/Mg3 (Sb, Bi)2 including the filling factor and the number of leg pairs, both the electrical and thermal energy losses are reduced. A record conversion efficiency of 8.2% is realized under a temperature difference of 260 K, thus fulfilling 90% of the theoretical efficiency of the materials and transcending the Bi2 Te3 modules.